2014
DOI: 10.11607/jomi.3621
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Comparison of the Retentive Properties of Ball and Locator Attachments for Implant Overdentures

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(73 citation statements)
references
References 0 publications
11
55
0
Order By: Relevance
“…The data collected in in vitro studies [21,27,33] showed differences between the retention or distribution of forces. Some authors suggest that the retention of the overdenture changes over time due to wearing of the attachments.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The data collected in in vitro studies [21,27,33] showed differences between the retention or distribution of forces. Some authors suggest that the retention of the overdenture changes over time due to wearing of the attachments.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggest that the retention of the overdenture changes over time due to wearing of the attachments. Systems like the locator and metal bar are less likely to wear over time, even after the simulation of 5000 cycles of insertion [21]. Therefore, they should have a better clinical outcome than ball attachments and magnets [10,11,21,27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations